Development Of Animated Video Learning Media Based On The Flipaclip Application Class VII On Classification Of Living Creatures Material At SMPN 21 Bengkulu City - Safta Yudha Pratama; Adisel; Fadilah (Universitas Muhammadiyah Sumatera Utara, 2024)
Study This aim For know what are the steps? design animation video development science based learningb Flipaclip there is material on the lassification of living things, how about it feasibility of animated video based science learning Flipaclip on the material of classification of living creatures , and the effectiveness of animated videos science- basedl earning Flipaclip on the material classification of living things fors tudents of SMPN 21 Bengkulu City. Type of research used that is Riesearch iand Development i(R&D). iDevelopment model used in study This s ithe ADDIE model consisting of from (Analysis, Design,Development,Implementation, and Evaluation).Results of developing interactive sciencel earning videos based Flipaclip principal discussion of material andchanges in class VII SMP grades from validation expert language as big 96.1%, material experts 70% and media experts 70% 81.81% with Very worthy category. Questionnaire results teacher responses were 88.3% ands tudents amounting to 82.87% with Very worthy category. Whereas to teste ffectiveness done testing hypothesis with Sig. (2-tailed)<0.05 show existss ignificant difference before and after use of animated videos science based learning Flipaclip And has tested that science learning videos are interactive based on the Flipaclip system very effective used as a learning medium